(untitled) (Journal of Kathmandu Medical College, 2023)
Background: Hand grip strength is a simple procedure of assessing the function of hand and forearm. It can be used as a tool to evaluate nutritional status of individual, neurological disorder and to assess the post-operative status of the patient. The grip strength is affected by different variables such as geographical variation, gender, height, weight, body mass index and handedness of the individual. Objective: This study aims to correlate hand grip strength with gender, height, weight, body mass index and handedness among Nepali population. Methods: The study was analytical cross-sectional study conducted in students of Kathmandu University School of Medical Sciences. Convenience sampling was used. The height of the participants was taken by using Stadiometer in centimeter and weight was taken by using weighing machine in kilogram and body mass index was calculated. Hand grip strength was obtained by using Dynamometer measured in kilogram. The data were entered in Microsoft Excel Sheet and analysis was done in SPSS version 16.0. Results: Hand grip strength showed moderate positive correlation with both height and weight both in both dominant and non-dominant hands. Hand grip strength was positively correlated in underweight, normal weight and obese category of body mass index whereas overweight category was negatively correlated. Conclusion: Hand grip strength shows correlation with the gender, height, weight and body mass index.